The Possible Role of Helicobacter pylori Infection in Non-alcoholic Fatty Liver Disease - Cheng, Dan-dan; He, Cong; Ai, Hong-hui; Huang, Ying; Lu, Nong-hua (Frontiers in Microbiology, 2017)
Helicobacter pylori (H. pylori) which colonizes the stomach can cause a wide array of gastric disorders, including chronic gastritis, peptic ulcer and gastric cancer. Recently, accumulating evidence has implicated H. pylori infection in extragastrointestinal diseases such as cardiovascular diseases, neurological disorders, and metabolic diseases. At the same time, many scholars have noted the relationship between H. pylori infection and non-alcoholic fatty liver disease (NAFLD). Despite the positive association between H. pylori and NAFLD reported in some researches, there are opposite perspectives denying their relationship. Due to high prevalence, unclear etiology and difficult treatment of NAFLD, confirming the pathogenicity of H. pylori infection in NAFLD will undoubtedly provide insights for novel treatment strategies for NAFLD. This paper will review the relationship between H. pylori infection and NAFLD and the possible pathogenic mechanisms.